Community Group Networking on the Community-based Adaptation Measure in Tapak Village, Semarang Coastal Area - Bintang Septiarani; Wiwandari Handayani (Indonesian Journal of Geography, 2020)
The north coast of Central Java is one of the most vulnerable regions to climate change in Indonesia. Various activity in coastal area also leads to the growing of informal sector that closely related to the growing number of poor people in coastal area. Therefore, the loss of livelihood triggers the awareness of stakeholder to help people through Community-based Adaptation (CBA) in Semarang coastal area. This paper aims to elaborate on the importance of networking aspect in CBA that works in Semarang Coastal Area. Scope area of this research is Tapak Village which regarded as a pilot area of CBA implementation in Semarang. Stakeholders mapping and social network analysis was used to visualizing the community interaction in their adaptation measures. The purposive sample in interviewing CBA stakeholders is used to support the stakeholder analysis using Gephi 0.9 software. The finding shows that the existence of networks between the community and the relevant stakeholders such as NGO and local government also became one of the supporting factors for the sustainability of community-based adaptation approach in coastal areas of Semarang City.